The pet dragon : a story about adventure, friendship, and Chinese characters - Niemann, Christoph (Greenwillow Books, 2008)
When Lin's beloved pet dragon disappears, she searches for him far and wide until a witch helps her to reach the dragon's new home. Introduces a different Chinese character on each step of Lin's adventure.